Implementasi Media Puzzle Stick pada Minat dan Keterampilan Membaca Permulaan Kelas II Sekolah Dasar - Alif Lifia Ade Pertiwi; Rila Melyana Fitri; Muamar Muamar (Departement of Mathematics Education, 2023)
This research aims to determine the results of implementing puzzle stick media on the interest and initial reading skills of class II elementary school students. The research approach is quantitative, quasi-experimental methods with a nonequivalent control group design. The sampling technique used is a saturated sampling technique which uses the entire population as the sample in the research. The data obtained came from questionnaires and tests. Questionnaire sheets are used to collect reading interest data and tests are used to collect data on initial reading skills. This research was analyzed using hypothesis testing, namely the sample t-test using the gain score. The results of data analysis were obtaining the mean of the experimental and control classes using the gain score. In terms of interest, the experimental class obtained an average gain score of 10.90 and 7.15 for the control class. The results of the average gain score for interest in reading show that the experimental class average is 3.75 greater than the control class. Meanwhile, in the initial reading skills data, the average gain score in the experimental class was 19.86 and 11.50 for the control class. The results of the average gain score for initial reading skills show that the experimental class average is 8.36 greater than the control class. For the independent sample t-test hypothesis test results, the gain score is used as follows: (1) The results of data analysis show significant results, as evidenced by the t test results obtained with a t value of 2.083 > t table 2.022 and a sig value of 0.044 < 0 .05 then Ho is rejected and Ha is accepted. Which means, there is a significant increase in interest in reading by implementing the puzzle stick media. (2) The t test results obtained a t value of 4.641 > t table 2.022 and a sig value of 0.000 < 0.05, so Ho was rejected and Ha was accepted. There is a significant increase in beginning reading skills by implementing the stick puzzle media.